Predisposing factors for anti‐D immune response in D− patients with chronic liver disease transfused with D+ platelet concentrates. Issue 4 (3rd January 2019) - Burin des Roziers, Nicolas; Chadebech, Philippe; Malard, Lucile; Vingert, Benoit; Gallon, Philippe; Samuel, Didier; Djoudi, Rachid; Fillet, Anne‐Marie; Pirenne, France
Abstract : BACKGROUND: Recent reports have indicated that the risk of anti‐D alloimmunization following D‐incompatible platelet (PLT) transfusion is low in hematology and oncology patients. We investigated the rate of anti‐D alloimmunization in RhD‐negative (D − ) patients with chronic liver disease transfused with D + platelet concentrates (PCs) and the factors involved, at a liver transplant (LT) center. STUDY DESIGN AND METHODS: We reviewed the blood bank database from January 2003 to October 2016. D − patients who had received D + PLT transfusions were eligible if they had undergone antibody screening at least 28 days after the first D + PC transfusion, had no previous or concomitant exposure to D + blood products, and had not received anti‐D immunoglobulins. RESULTS: Six of the 56 eligible patients (10.7%) had anti‐D antibodies. All had received whole blood‐derived PCs. Four of 20 patients (20%) untransplanted or transfused before LT and only two of 36 patients (5.6%) transfused during or after LT produced anti‐D antibodies. These two patients were on maintenance immunosuppression based on low‐dose steroids and tacrolimus. The factors identified as significantly associated with anti‐D immune response were the presence of red blood cell immune alloantibodies before D + PLT transfusion (p = 0.003), and D + PLT transfusion outside the operative and postoperative (5 days) periods for LT (p = 0.023). CONCLUSION: D − patients with chronic liver disease transfused with D + PLTs before LT are at high risk of developing anti‐D antibodies. Preventive measures should be considered for these patients.